Tracking GPS location through network connection / Intan Huzalyny Hussin and Mohammad Hafiz Mohd Yusof - Hussin, Intan Huzalyny; Mohd Yusof, Mohammad Hafiz (2024)
GPS (Global Positioning System) technology is ubiquitous in modern life. It provides location data for navigation, mapping, and various applications to the users. While GPS itself relies on satellite signals, its usefulness often hinges on network connectivity. Hence, this paper explores how network connections are used to track GPS data and the implications of this practice.